Perfluoropolyethers in the Prevention of Irritant Contact Dermatitis - Elsner, P.; Wigger-Alberti, W.; Pantini, G. (Dermatology (Basel), 1998)
Background: Perfluoropolyethers (PFPEs) are non-reactive perfluorinated (no hydrogen atoms) liquid polymers that showed promise as ingredients of protective preparations in occupational dermatology. Objective: The aim of this study was to investigate if oil-in-water (o/w) emulsions containing 0.5, 1.0, 2.0 and 4.0% PFPEs (molecular weight 6,250 D) prevent epidermal barrier disruption induced by a repetitive irritation test (RIT). Methods: PFPE-containing o/w emulsions and the emulsion base alone were evaluated against a set of 4 irritants [10% sodium lauryl sulphate (SLS), 0.5% sodium hydroxide (NaOH), 15% lactic acid (LA), and undiluted toluene (TOL)] in the RIT. Ten subjects were tested on the paravertebral skin of the mid-back. Irritation was assessed by visual scoring, transepidermal water loss (TEWL) and colorimetry. Results: Both the emulsion base and all PFPE-containing preparations significantly suppressed irritation by SLS and NaOH. Against LA and TOL, only the 4% PFPE-containing preparation was significant as assessed by TEWL. Conclusion: A 4% PFPE-containing o/w emulsion significantly inhibits irritation due to a wide spectrum of hydrophilic and lipophilic irritants. o/w emulsions with lower concentrations of PFPE are also effective against SLS and NaOH, but this is also true for the cream base alone. Therefore, further studies are necessary to evaluate if a minimum of 4% PFPE in the base provides additional benefit.